MOBILE BANKING: ANALISA PENGGUNAAN PADA NASABAH PT. BANK ACEH SYARIAH CABANG LHOKSEUMAWE: PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Rahmawati, Rahmawati (Fakultas Ekonomi dan Bisnis Islam, 2019)
Mobile banking offers convenience in conducting banking transactions. Customers who use mobile banking will get customer information in conducting banking transactions. PT Bank Aceh Syariah Lhokseumawe Branch Lhokseumawe Branch, as one of the banking institutions, is well aware that service to customers must be adjusted to advance technological outlook. This study limits only using three factors and needs to be considered by researchers, because the Technology Acceptance Model (TAM) as a model of user acceptance in an information system. Based on this analysis it is known that or a constant of 92.343% means the three variables namely Perception of Ease, Comfort, and Trust has an influence on the preference variable of 21.453%, the regression coefficient of perceived convenience variable (X1) of 55.7%, the regression coefficient of comfort variable (X2) of 27.9%, and the regression coefficient of the trust variable (X3) of 93.8%. Based on the results of the F-Test and T-test, it can be seen that the most dominant factor influencing customer interest in using mobile banking is the trust factor because the value of the trust variable is greater than that of other variables.